Perlindungan Hukum terhadap Pelaku Usaha Akibat Pembatalan Sepihak oleh Konsumen dalam Jual Beli Melalui Sistem Cash On Delivery : Studi Penelitian Kota Jambi - Meriskan Dwi Zalyanti; Ruliati Ruliati; Nurhayati Nurhayati; Rafli Ardiansyah; Ilham Ilham; Ika Dwimaya Roza (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid development of information technology has significantly increased the practice of online buying and selling as part of electronic commerce (e-commerce). One of the payment methods widely used in online transactions is cash on delivery (COD), in which payment is made by the consumer at the time the goods are received. Although the COD system provides convenience and a sense of security for consumers, in practice it often gives rise to legal problems, particularly unilateral cancellations by consumers. Such cancellations are frequently carried out after the goods have been shipped or have arrived at the destination address, resulting in material and non-material losses for business actors. This condition indicates an imbalance in legal protection between consumers and business actors in online transactions using the COD system. This study aims to analyze the mechanism of implementing the COD payment system in online buying and selling transactions and to examine the forms of legal protection available for business actors affected by unilateral cancellations by consumers. This research employs an empirical juridical method, also known as sociological legal research, with a field research approach to examine the application of law in practice, particularly in Jambi City. Data were collected through literature review and interviews and analyzed qualitatively. The findings of this study are expected to contribute to the development of legal regulation and to strengthen legal certainty and protection for business actors in online transactions.